Barry, the bravest Saint Bernard - Hall, Lynn.; Castro, Antonio, 1941- (New York : Random House, 1992)
Relates the feats of Barry, the St. Bernard dog whose name, to this day, honors the best dog at the St. Bernard Monastery.
550
Accelerated Reader AR
Keywords: Barry (Dog) -- Juvenile literature; Saint Bernard dog -- Switzerland -- Biography -- Juvenile literature; Rescue dogs -- Switzerland -- Biography -- Juvenile literature; Barry (Dog); Saint Bernard dog; Dogs